Mothers on Display: Lunchboxes, Social Class and Moral Accountability. (August 2015) - Harman, Vicki; Cappellini, Benedetta
This article explores middle class mothers' narratives on their daily routines of preparing lunchboxes for their children. In this study lunchboxes are understood as an artefact linking together discourses and practices of doing and displaying mothering, media and government discourses of feeding children and broader issues of care and surveillance in private and public settings. Drawing on semi-structured, photo elicitation interviews and a focus group discussion, this article illuminates how mothers feel on display through the contents of their children's lunchboxes.